2004
DOI: 10.1128/jvi.78.5.2255-2264.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of Protective CD8+T-Cell Responses Driven by Recombinant Cytomegaloviruses

Abstract: CD8؉ T cells are critical for the control of many persistent viral infections, such as human immunodeficiency virus, hepatitis C virus, Epstein-Barr virus, and cytomegalovirus (CMV). In most infections, large CD8؉ -T-cell populations are induced early but then contract and are maintained thereafter at lower levels. In contrast, CD8؉ T cells specific for murine CMV (MCMV) have been shown to gradually accumulate after resolution of primary infection. This unique behavior is restricted to certain epitopes, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
123
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 103 publications
(130 citation statements)
references
References 66 publications
7
123
0
Order By: Relevance
“…However, epitopes in the C57BL/6 model (ie, restricted by H‐2b as opposed to H‐2d) were not yet described. Using a recombinant virus expressing well‐described epitopes from influenza nucleoprotein (NP) and LCMV glycoprotein (GP) expressed at the C terminus of the immediate early 2 (IE2) molecule (which is redundant for full viral replication), C57BL/6 mice were infected and immune responses tracked over time 2. In fact, the initial results were rather disappointing, since acutely very little was seen.…”
Section: The Origins Of Memory Inflationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, epitopes in the C57BL/6 model (ie, restricted by H‐2b as opposed to H‐2d) were not yet described. Using a recombinant virus expressing well‐described epitopes from influenza nucleoprotein (NP) and LCMV glycoprotein (GP) expressed at the C terminus of the immediate early 2 (IE2) molecule (which is redundant for full viral replication), C57BL/6 mice were infected and immune responses tracked over time 2. In fact, the initial results were rather disappointing, since acutely very little was seen.…”
Section: The Origins Of Memory Inflationmentioning
confidence: 99%
“…The first point is that it depends on the viral context, since epitopes which show inflation in the adenovirus or MCMV models do not induce inflation if presented in other recombinant settings such as vaccinia viruses—in other words it is not an inherent property of the peptide (for example related to some aspect of cross‐reactivity) 16, 22. Within a given model where inflation can occur, the answer does not appear to be related to initial immunodominance, since even very subdominant responses can inflate at later time‐points 2, 3, 4, 71. Similarly, it is not dependent on the affinity of the epitope itself for MHC, since responses to the same epitope can be converted from a non‐inflationary to an inflationary type by modulating the epitope context 2, 3, 71…”
Section: Mechanisms Underlying Memory Inflationmentioning
confidence: 99%
See 2 more Smart Citations
“…The cloning of CMV as bacterial artificial chromosomes (BAC) in Escherichia coli (6) allowed quick and efficient targeted mutagenesis of the CMV genome, as well as the generation of CMVs expressing defined heterologous target Ags (7). Initial results showed that these recombinants were able to induce T cell responses to peptides derived from other viruses, such as influenza A or lymphocitic choriomeningitis virus (7), and that provided immune protection against recombinant poxviruses expressing the target Ag.…”
mentioning
confidence: 96%